2017
DOI: 10.1002/mp.12466
|View full text |Cite
|
Sign up to set email alerts
|

Portable perfusion phantom for quantitative DCEMRI of the abdomen

Abstract: Purpose To develop a portable perfusion phantom and validate its utility in quantitative dynamic contrast-enhanced magnetic resonance imaging of the abdomen. Methods A portable perfusion phantom yielding a reproducible contrast enhancement curve (CEC) was developed. A phantom package including perfusion and static phantoms were imaged simultaneously with each of three healthy human volunteers in two different 3T MR scanners. Look-up tables correlating reference (known) contrast concentrations with measured o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…Phantom quality control may ensure adequate precision and reproducibility in T 1 measurements, a prerequisite for performing quantitative DCE analysis. It also allows for the measurement of the contrast response of the employed DCE acquisition sequence across a range of T 1 relaxation rates observed in in vivo DCE studies and the stability of that contrast response over time and across system upgrades …”
Section: Precision Metrologymentioning
confidence: 99%
See 3 more Smart Citations
“…Phantom quality control may ensure adequate precision and reproducibility in T 1 measurements, a prerequisite for performing quantitative DCE analysis. It also allows for the measurement of the contrast response of the employed DCE acquisition sequence across a range of T 1 relaxation rates observed in in vivo DCE studies and the stability of that contrast response over time and across system upgrades …”
Section: Precision Metrologymentioning
confidence: 99%
“…In addition to static T 1 phantoms, some investigators have developed dynamic phantoms for MRI (Kim et al), and computed tomography (CT) (Driscoll et al). The recent perfusion phantom was developed to correct MR scanner‐dependent variations in estimates of the tissue perfusion parameters in the abdomen . The design of Kim et al is shown in Fig.…”
Section: Precision Metrologymentioning
confidence: 99%
See 2 more Smart Citations
“…With DSC‐MRI, validation efforts have included in vivo comparisons of blood volume and blood flow measures to those derived from positron emission tomography (PET) and single photon emission computed tomography (SPECT), histology, and synthetic patient datasets . Similarly, numerous studies have validated DCE‐MRI methods using physical phantoms, and parameters in different organs using autoradiography, histology, and DCE computed tomography (CT) . There is also an extensive literature validating cerebral perfusion measures from ASL using [ 15 O]‐water PET .…”
Section: Quantitatively Interrogating Biologymentioning
confidence: 99%